Inhibition of Osteoclast Differentiation by Carotenoid Derivatives through Inhibition of the NF-κB Pathway - Shlomit Odes-Barth; Marina Khanin; Karin Linnewiel-Hermoni; Yifat Miller; Karina Abramov; Joseph Levy; Yoav Sharoni (MDPI AG, 2020)
The bone protective effects of carotenoids have been demonstrated in several studies, and the inhibition of RANKL-induced osteoclast differentiation by lycopene has also been demonstrated. We previously reported that carotenoid oxidation products are the active mediators in the activation of the transcription factor Nrf2 and the inhibition of the NF-κB transcription system by carotenoids. Here, we demonstrate that lycopene oxidation products are more potent than intact lycopene in inhibiting osteoclast differentiation. We analyzed the structure-activity relationship of a series of dialdehyde carotenoid derivatives (diapocarotene-dials) in inhibiting osteoclastogenesis. We found that the degree of inhibition depends on the electron density of the carbon atom that determines the reactivity of the conjugated double bond in reactions such as Michael addition to thiol groups in proteins. Moreover, the carotenoid derivatives attenuated the NF-κB signal through inhibition of IκB phosphorylation and NF-κB translocation to the nucleus. In addition, we show a synergistic inhibition of osteoclast differentiation by combinations of an active carotenoid derivative with the polyphenols curcumin and carnosic acid with combination index (CI) values < 1. Our findings suggest that carotenoid derivatives inhibit osteoclast differentiation, partially by inhibiting the NF-κB pathway. In addition, carotenoid derivatives can synergistically inhibit osteoclast differentiation with curcumin and carnosic acid.